Ups and downs - Buenaventura, Patricia Gabrielle S.; Lee, Gabriela Alejandra D. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2018)
Children's fiction is a tool to expose children to new experiences while teaching valuable life lessons. Recently, children's fiction began opened itself up to being more than just a tool for education but also for breaking down barriers and changing perceptions. In particular, children's fiction has become a medium where PWDs can promote awareness about their experiences as well as influence them to have a positive way of looking at PWDs. This paper attempts to present the current perceptions of Filipinos towards PWDs, explain how children's fiction can be used as a tool for awareness and influence, stress the importance of crafting characters with disabilities positively and realistically, as well as provide ways to craft these characters as such.
Thesis (B.A. in Creative Writing)--University of the Philippines Diliman